Intelligence sharing, transnational organized crime and multinational peacekeeping - Chido, Diane E. (Palgrave pivot, 2018)
Introduction -- Why worry about organized crime? -- United Nations intelligence and transnational organized crime initiatives : evolution and lessons learned -- BAIT : analytic model for catching bad guys and addressing intelligence limitations